2019
DOI: 10.1055/a-0983-2271
|View full text |Cite
|
Sign up to set email alerts
|

Darstellung von retinalen Neovaskularisationen mit der optischen Kohärenztomografie-Angiografie im Vergleich mit der Fluoreszeinangiografie

Abstract: Zusammenfassung Zielsetzung Vergleichende Darstellung von retinalen papillären (NVD) und nicht papillären (NVE) Neovaskularisationen in der optischen Kohärenztomografie-Angiografie (OCTA) und in der Fluoreszeinangigrafie (FA) bei Patienten mit proliferativer diabetischer Retinopathie. Material und Methoden 15 konsekutive Patienten wurden in diese Studie aufgenommen. Alle Patienten erhielten eine OCTA, wobei jeweils ein Scan von 3 × 3 mm der „Region of Interest“ mit dem ZEISS OCT Cirrus 5000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
0
1
Order By: Relevance
“…In this study, we did not find a correlation between area by OCT-A and FA [ 20 ]. This is in conflict with a previous study on this topic that found a good correlation of area measured by the two methods [ 21 ]. When measuring area of retinal NVs by OCT-A the measurements are only done of the relevant diseased vessels.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we did not find a correlation between area by OCT-A and FA [ 20 ]. This is in conflict with a previous study on this topic that found a good correlation of area measured by the two methods [ 21 ]. When measuring area of retinal NVs by OCT-A the measurements are only done of the relevant diseased vessels.…”
Section: Discussioncontrasting
confidence: 99%